Developing In Vitro-In Vivo Correlation (Ivivc) For Trimetazidine, Indapamide And Ciprofloxacin Extended-Release Solid Oral Dosage Forms - I. E. SHOHIN; G. V. RAMENSKAYA; A. Y. SAVCHENKO (International Journal of Pharma and Bio Sciences, 2011)
The current paper describes in vitro-in vivo correlation (IVIVC) development for extended-release solid oral dosage forms containing BCS Class I, II and III APIs: trimetazidine, indapamide and ciprofloxacin. Dissolution kinetics (in 3 media: 0.1 M or 0.01 M hydrochloric acid, acetate buffer pH 4.3, phosphate buffer pH 6.8) and pharmacokinetic properties of evaluated drugs were studied. Level B IVIVC was established for each of evaluated solid oral dosage forms, correlation coefficients (r) were 0.97, 0.94 and 0.96 for trimetazidine, indapamide and ciprofloxacin drugs, respectively.